Pain management : - Main, Chris J. (Churchill Livingstone, 2001)
(Churchill Livingstone) Univ. of Manchester, UK. Deals specifically with the management of potentially chronic pain, how to assess patients with pain, the factors involved in the development of chronic pain, and the setting up and running of a pain management program. For students and health professionals.